answersLogoWhite

0


Best Answer

-6 x -3 = 18 + (-6) = 12

User Avatar

Wiki User

โˆ™ 2010-10-26 01:16:44
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: What is minus 6 times minus 3 add minus 6?
Write your answer...
Submit
Related questions

What is -6x plus 3 equals -57?

x = 10 Minus 6 times 10 = minus 60 Add 3 to minus 60 = minus 57


What is the answer of the absolute value if you add -3 add -3?

-6


What is minus 2 times 3?

minus 6


What can you add to 9 to make it 6?

-3 (minus 3)


What is minus 8 times minus 3 plus minus 6 equals?

18


How much is 3 times 3 minus 3?

6...


What is 6 times minus 2 times one third?

6-2/3=16/3


What is minus 6 times minus 11 add minus 22?

The answer is 44. -6 * -11 = 66 66 + -22 = 44


What is 3 plus 4 times 9 minus 6?

First you multiply 4 and 9, which you get 36 then you add the 3, which makes 39 and then subtract 6... leaving you with an answer of 33. :)


What is minus 6 minus minus 3?

-6--3=3


What is the difference between minus 6 times minus 3 and minus 10 times minus 9?

(-6) x (-3) = 18 (-10) x (-9) = 90 18 - 90 = -72


What is 4 times 6 minus 3?

4 x 6 - 3 = 21


What is -2 times -3?

1


Simmplify the expression -6 times 12 plus 14 minus 3?

-6 times 12 plus 14 minus 3 is equal to -61.


What is the repeated subtraction for 9 divided by 3?

6


What is 15 plus 3 minus 6 times 4?

15 + 3 - (6 x 4) = -6


What is three times minus two?

3*(-2) = -6


What is Three minus three times 6 plus 2 and how do you get the answer?

If you mean: 6 times (3-3) plus 2 then the answer is 2


What is 6 times 8 minus 6 plus 3 minus 7?

6*8-6+3-7 =48-6+3-7 =48-3-7 =38


What does a plus add a minus equal?

When you have two different signs together (a plus and a minus) the minus takes precedence (the minus "wins"). So, for example, 9 + -3 = 9 - 3 = 6.


What is 3 minus 3 times 6 plus 2?

It is: (3-3) times (6+2) = 0


What is 5 times 7 divided by 5 plus 3 minus 4?

5 times 7 divided by 5 plus 3 minus 4 is 6.


Can you use 3 times 6 to find 7 times 6?

Yes, if you add 6 four more times to the product you got with 6 times 3.


What is 3-3x6 plus 2?

3 minus 3 times 6 plus 2 =


What is six times three minus three?

6 x 3 - 3 = 15